Comparison of early outcomes of arthroscopic labral repair or debridement: a study using the UK Non-Arthroplasty Hip Registry dataset. (1st April 2022) - Holleyman, Richard James; Lyman, Stephen; Bankes, Marcus J. K.; Board, Tim Nicholas; Conroy, Jonathan Lee; McBryde, Callum Wilson; Andrade, Antonio Jose; Malviya, Ajay; Khanduja, Vikas
Abstract : Aims: This study uses prospective registry data to compare early patient outcomes following arthroscopic repair or debridement of the acetabular labrum. Methods: Data on adult patients who underwent arthroscopic labral debridement or repair between 1 January 2012 and 31 July 2019 were extracted from the UK Non-Arthroplasty Hip Registry. Patients who underwent microfracture, osteophyte excision, or a concurrent extra-articular procedure were excluded. The EuroQol five-dimension (EQ-5D) and International Hip Outcome Tool 12 (iHOT-12) questionnaires were collected preoperatively and at six and 12 months post-operatively. Due to concerns over differential questionnaire non-response between the two groups, a combination of random sampling, propensity score matching, and pooled multivariable linear regression models were employed to compare iHOT-12 improvement. Results: A total of 2, 025 labral debridements (55%) and 1, 659 labral repairs (45%) were identified. Both groups saw significant (p < 0.001) EQ-5D and iHOT-12 gain compared to preoperative scores at 12 months (iHOT-12 improvement: labral repair = +28.7 (95% confidence interval (CI) 26.4 to 30.9), labral debridement = +24.7 (95% CI 22.5 to 27.0)), however there was no significant difference between procedures after multivariable modelling. Overall, 66% of cases achieved the minimum clinically important difference (MCID) and 48% achieved substantial clinical benefit at 12 months. Conclusion: Both labral procedures were successful in significantly improving early functional outcome following hip arthroscopy, regardless of age or sex. Labral repair was associated with superior outcomes in univariable analysis, however there was no significant superiority demonstrated in the multivariable model. Level of evidence: III Cite this article: Bone Jt Open  2022;3(4):291–301.